Digital literacy and the 4c competencies as the foundation of education 4.0 transformation in Indonesia: a conceptual review - Agus Junsion Naibaho; Eduardo Sianturi (Lembaga Riset Mutiara Akbar, 2026)
The transformation of education in the era of the Fourth Industrial Revolution has shifted learning paradigms toward adaptive, technology-enhanced, and competency-based education. This study aims to examine the conceptual relationship between digital literacy and the four core twenty-first-century competencies (4Cs)—critical thinking, creativity, collaboration, and communication—as the foundation of Education 4.0 in Indonesia. A conceptual review approach was employed by synthesizing international journal articles, policy documents, and authoritative reports relevant to digital literacy, Education 4.0, and twenty-first-century learning. The data were analyzed through thematic analysis and conceptual synthesis. The findings indicate that digital literacy has evolved into a multidimensional competency encompassing technical, cognitive, social, ethical, and epistemic dimensions that support the development of the 4C competencies. However, the implementation of Education 4.0 in Indonesia continues to face challenges related to digital inequality, teachers' digital competence, curriculum adaptation, and educational technology governance. This study proposes the Humanistic Digital Learning Ecosystem Model, integrating digital literacy, the 4C competencies, constructivist pedagogy, ethical artificial intelligence, and local wisdom as a conceptual framework for advancing Education 4.0 in Indonesia.